Some properties of a generalized multiplier transform on analytic $p$-valent functions - Hamzat, J. O.; El-Ashwah, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5For a function $$f(z)=z^{p}+\sum^{∞}_{k=1} a_{k+p}z^{k+p},$$ where $p\in\mathbb{N},$ the authors investigate some properties of a more general multiplier transform on analytic $p$-valent functions in an open unit disk. The applications of the obtained results to fractional calculus are pointed out, while several other corollaries follow as simple consequences.